GAMBARAN PERFORMA DOKTER UMUM DAN DOKTER SPESIALIS SEBAGAI INSTRUKTUR SKILLS LAB DI FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA - lidya Bethsi Evangeline Saptenno (Fakultas Kedokteran Universitas Pattimura, 2023)
Introduction: Skills lab is a means for pre-clinical students to learn and practice clinical skills. In the learning process, an instructor is needed who is responsible for facilitating the mentoring process. Those who act as skills lab instructors at the Faculty of Medicine, University of Pattimura are general practitioners and specialist doctors. To support their role, an instructor needs basic knowledge and skills in providing clinical skills training. This research was conducted to describe the performance of skills lab instructors at the Faculty of Medicine, Pattimura University. Method: This research is a quantitative descriptive study using a questionnaire that has been adopted from the